2002
DOI: 10.6009/jjrt.kj00000921550
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Simulation with Multi-slice CT for Laparoscopic Nephrectomy

Abstract: In recent years, laparoscopic surgery has attracted attention as a minimally invasive type of surgery because of the small surgical wounds and early recovery it provides. We carry out this technique on the basis of volume data that we make use of in multi-slice CT imaging technology in laparoscopic nephrectomy by the retroperitoneal approach, and we have created CT virtual laparoscopy by virtual endoscopic display as an intra-operative navigatior with an image analysis system. We provide information on detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Some reports suggested that a slice thickness of about 2mm is required to construct clear 3D images [12,13]. At present, we are trying to combine the CT data (precontrast image, arterial phase, and nephrographic phase) and to improve the software so that tumors, vessel trees, or urinary ducts are highlighted in the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that a slice thickness of about 2mm is required to construct clear 3D images [12,13]. At present, we are trying to combine the CT data (precontrast image, arterial phase, and nephrographic phase) and to improve the software so that tumors, vessel trees, or urinary ducts are highlighted in the simulation.…”
Section: Discussionmentioning
confidence: 99%